The Transformative Role of AI in Advertising and Marketing: From Data-Driven Practices to Virtual Experiences - Ramachandran, Ramakrishnan; Pillai, Sruthi; Dahal , Ram Krishna (Journal of Innovation in Academia, 2025)
Artificial Intelligence (AI) has fundamentally transformed advertising and marketing by enabling data-driven hyper-personalization and predictive capabilities. This systematic literature review, based on 98 peer-reviewed studies (2018–2024) and guided by PRISMA, explores AI’s evolving role, from analyzing consumer behavior to enabling automated ad creation, dynamic segmentation, and real-time optimization. Findings reveal that AI enhances conversion rates while reducing costs by leveraging tools like generative AI for text/visual ads and predictive analytics for customer insights. The study highlights AI's shift from transactional to relational marketing, emphasizing its capacity to foster long-term customer relationships through personalized messaging and immersive Metaverse experiences. However, challenges such as algorithmic bias, privacy concerns, and SME adoption barriers persist, necessitating ethical frameworks like Explainable AI (XAI) for transparency. The study extends Relationship Marketing and Resource-Based View (RBV) theories to AI-driven environments and offers practical guidance on integrating AI while preserving human creativity.